Robust adaptive tracking for Markovian jump nonlinear systems with unknown nonlinearities - Jin Zhu; Hong-Sheng Xi; Hai-Bo Ji; Bing Wang (Discrete Dynamics in Nature and Society)
Robust adaptive tracking problems for a class of Markovian jump parametric-strict-feed-back systems with both parametric uncertainty and unknown nonlinearity are investigated. The unknown nonlinearities considered herein lie within some “bounding functions,” which are assumed to be partially known. By using a stochastic Lyapunov method and backstepping techniques, a parameter adaptive law and a control law were obtained, which guarantee that the tracking error could be within a small neighborhood around the origin in the sense of the fourth moment. Moreover, all signals of the closed-loop system could be globally uniformly ultimately bounded.